Thyroid Hormone Action: Astrocyte–Neuron Communication - Morte, Beatriz; Bernal, Juan (Frontiers in Endocrinology, 2014)
Thyroid hormone action is exerted mainly through regulation of gene expression by binding of T3 to the nuclear receptors. T4 plays an important role as a source of intracellular T3 in the central nervous system via the action of the type 2 deiodinase, expressed in the astrocytes. A model of T3 availability to neural cells has been proposed and validated. The model contemplates that brain T3 has a double origin: a fraction is available directly from the circulation, and another is produced locally from T4 in the astrocytes by type 2 deiodinase. The fetal brain depends almost entirely on the T3 generated locally. The contribution of systemic T3 increases subsequently during development to account for approximately 50% of total brain T3 in the late postnatal and adult stages. In this article we review the experimental data in support of this model, and how the factors affecting T3 availability in the brain, such as deiodinases and transporters, play a decisive role in modulating local thyroid hormone action during development.